Analisis Penggunaan Bahasa Gaul dalam Pemahaman Istilah Ekonomi Formal pada Mahasiswa Pendidikan Ekonomi Universitas Negeri Gorontalo - Angelita Rizqia Saleh; Siti Rahmawati; Ni Komang Parniati; Natalia Huko; Delfita Hamid; Rahmatia Ramadhani Hi. Ali; Lutvia Rahman; Amelia Lapatu; Suci Yani Anwar; Arif Prasetyo Katili; Patrio Pakaya; Meilina Widya Dali (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the use of slang in relation to the understanding of formal economic terms among Economics Education students at Gorontalo State University. The study employed a descriptive qualitative approach, involving 11 second-semester students as informants selected using purposive sampling. Data collection was conducted through semi-structured interviews, followed by analysis using data reduction, data presentation, and conclusion-drawing techniques. The results of the study indicate that slang is more frequently used by students in daily communication and informal academic discussions because it is considered more relaxed and easier to understand. Students also simplify formal economic terms into everyday language, such as the term “inflation,” which is explained as “prices of all goods are rising” to make it easier to understand during discussions. The use of simple language helps students understand economic concepts in the early stages of learning, especially regarding economic terms that are rarely used in daily life. Nevertheless, the use of formal Indonesian is still considered important in presentations, writing assignments, and academic communication because it relates to the accuracy of formal economic terminology.